Candidate Effects on Election Outcomes: Political Skill, Campaign Efficacy, and Intentions in a British General Election. Issue 4 (9th December 2020) - Silvester, Joanne; Wyatt, Madeleine; Ellen, B. Parker; Ferris, Gerald R.
Abstract : Integrating Social/Political Influence Theory with the Theory of Planned Behavior, we argue that personal resources (i.e., political skill, self‐efficacy) enable political candidates to form more ambitious campaign intentions, and thus perform better in elections. We tested this model with a sample of political candidates ( N  = 225) campaigning in a British general election. Three months before polling day, candidates provided self‐ratings of political skill, domain‐specific self‐efficacy (i.e., campaign efficacy), and personal campaign intentions during the campaign period. Our results demonstrated that political skill was positively related to campaign efficacy, and intentions, via campaign efficacy. We also found a significant indirect effect for political skill on electoral performance (i.e., percentage of the vote), through campaign efficacy and intentions. Implications of our results for understanding candidate effects in campaigns and future research are discussed.